Erythropoietin Neuroprotection with Traumatic Brain Injury - Ponce, Lucido L. (2012)
Numerous experimental studies in recent years have suggested that erythropoietin (EPO) is an endogenous mediator of neuroprotection in various central nervous system disorders, including TBI. Many characteristics of EPO neuroprotection that have been defined in TBI experimental models suggest that it is an attractive candidate for a new treatment of TBI. EPO targets multiple mechanisms known to cause secondary injury after TBI, including anti-excitotoxic, antioxidant, anti-edematous, and anti-inflammatory mechanisms. EPO crosses the blood brain barrier. EPO has a known dose response and time window for neuroprotection and neurorestoration that would be practical in the clinical setting. However, EPO also stimulates erythropoiesis, which can result in thromboembolic complications. Derivatives of EPO which do not bind to the classical EPO receptor (carbamylated EPO) or that have such a brief half-life in the circulation that they do not stimulate erythropoiesis (asialo EPO and neuro EPO) have the neuroprotective activities of EPO without these potential thromboembolic adverse effects associated with EPO administration. Likewise, a peptide based on the structure of the Helix B segment of the EPO molecule that does not bind to the EPO receptor (pyruglutamate Helix B surface peptide) has promise as another alternative to EPO that may provide neuroprotection without stimulating erythropoiesis.